Effectiveness of iStent Trabecular Microbypass System Combined with Phacoemulsification versus Phacoemulsification Alone in Patients with Glaucoma and Cataract Depending on the Initial Intraocular Pressure - Kozera, Milena; Konopińska, Joanna; Mariak, Zofia; Rękas, Marek (Ophthalmic research, 2021)
Introduction: To assess the effect of iStent trabecular microbypass implantation combined with phacoemulsification on intraocular pressure (IOP) and glaucoma medications and to compare this to outcomes of phacoemulsification alone in patients with mild to moderate primary open-angle glaucoma (POAG) depending on initial IOP. Materials and Methods: Eighty subjects with cataract and POAG were randomized 1:1 into either iStent implantation and cataract surgery (iStent group) (n = 44) or cataract surgery alone (control group) (n = 36). Groups were divided according to initial IOP (after washout period) into IOP <26 mm Hg and IOP ≥26 mm Hg. Patients were assessed preoperatively and at postoperative day 1, week 1, and months 1, 3, 6, 12, and 24. Outcome measures included best-corrected visual acuity, IOP, and glaucoma medications. Results: Postoperatively at 24 months, mean IOP decreased from 20.93 ± 1.28 to 17.79 ± 2.50 mm Hg in the IOP subgroup <26 mm Hg and from 26.00 ± 0.00 to 19.86 ± 2.19 in the subgroup ≥26 mm Hg in the control group. In the iStent group <26 mm Hg, IOP decreased from 22.04 ± 1.64 to 15.57 ± 2.13 mm Hg and from 26.6 ± 1.09 to 17.06 ± 2.43 mm Hg in the iStent group ≥26 mm Hg. Conclusion: In patients with open-angle glaucoma and cataract, iStent implantation combined with cataract surgery reduced IOP significantly through 2 years, with greater reductions achieved versus phacoemulsification alone. In patients with baseline IOP <26 mm Hg, surgery reduced IOP and medication use significantly declined through 2 years, with greater reductions achieved versus patients with baseline IOP ≥26 mm Hg. The study was registered at ClinicalTrials.gov under the number NCT03807869.